Impelemtasi Gerakan Literasi Sekolah (GLS) untuk Menumbuhkan Minat Baca Siswa di SMA Negeri 7 Banjarmasin - Diana, Diana; Juairiah, Juairiah (UIN Raden Intan Lampung, 2022)
Low reading skills will affect the quality of student learning which will have an impact on student achievement in school. To overcome these problems, SMA Negeri 7 Banjarmasin implement School Literacy Movement has been running from 2016 to the present. This is field research using a qualitative descriptive approach. Data collection techniques in this study used the methods of observation, interview, and documentation. The subjects in this study were the headmaster, Indonesian Subject teacher, homeroom teachers, and the librarian of SMA Negeri 7 Banjarmasin. The object of this research is the implementation of the School Literacy Movement to foster reading interest at SMA Negeri 7 Banjarmasin as well as the supporting and inhibiting factors for the implementation of the School Literacy Movement to foster reading interest in SMA Negeri 7 Banjarmasin. The data analysis process includes data reduction, data presentation, and drawing conclusions.The results of this study are as follows: 1. Implementation of School Literacy Movement at SMA Negeri 7 Banjarmasin is realized by implementing a socialization program for implementation of School Literacy Movement, reading literacy 15 minutes before starting the classes, library utilization, reading corner, literacy competition, writing Scientific Papers, as well as socialization and assistance to other schools. The implementation of the School Literacy Movement at SMA Negeri 7 Banjarmasin has been carried out all stages, but at the stage of development and learning does not hold follow-up literacy activities consistently and sustainably, so that the implementation is still in the habituation/interest growth stage. 2. Supporting factors: Adequate Human Resources, complete facilities and infrastructure, and funds. Inhibiting factors include low parental attention, low awareness, and willingness of students, and lack of coordination between teachers and the school management team.Keywords: School Literacy Movement, Reading Interest, Literacy, Library